Selenium Minerals and the Recovery of Selenium from Copper Refinery Anode Slimes - J. Fu (The Southern African Institute of Mining and Metallurgy, 2016)
"Since it was first identified in 1817, selenium has received considerable interest. Native selenium and a few selenium minerals were discovered several decades later. With the increasing number of selenium minerals, the occurrence of selenium minerals became the focus of much research. A great number of selenium deposits were reported all over the world, although few independent selenium deposits were discovered. Selenium is obtained mainly as a byproduct of other metals, and is produced primarily from the anode mud of copper refineries. This paper presents a comprehensive review of selenium minerals, as well as the treatment of copper refinery anode slimes for the recovery of selenium. Our focus is on the selenium minerals, including their discovery and occurrence, and the distribution of selenium resources. In addition, the main methods of recovering selenium from copper anode slimes are summarized. IntroductionSelenium (Se) was first observed in 1817 in a laboratory (Greenwood et al., 1984). The discovery of selenium was made by the Swedish chemist J.J. Berzelius and J.G. Gahn, who isolated selenium from a red residue in sulphuric acid from pyrite mined at Fahlun, Sweden. Selenium was named from the Greek word selene (moon), since it resembled tellurium, which had been discovered a few years earlier and named from the Latin word tellus (Earth).After the first observation of selenium in the laboratory, selenium received considerable interest. In 1954, E.P. Kaiser pointed out that Se is enriched in sulphide ores and often associated with Bi, Co, Sn etc. (Kaiser 1954). In 1959, Hawley and Nichol investigated selenium in Canadian sulphide minerals, and presented the content of selenium in sulphide from several deposits of different types. They also proposed that Se is enriched in lowtemperature hydrothermal pyrite (Hawley and Nichol, 1959). The thermodynamic conditions for forming native selenium and selenium minerals in sedimentary rocks were discussed, as well as geochemical behaviour of selenium near the oxidation zones of sulphides in the 1970s (Howard III, 1977; Zhu et al., 2003). Zhu et al. examined the morphology, features, and genesis of native selenium from Yutangba, Enshi City, Hubei Province, China in 2004, and pointed out, from the different forms of native Se, that selenium can be activated,transformed, remobilized, and enriched at sites such as in the unsaturated subsurface zone or in the saturated zone (Zhu et al., 2005). The transport and deposition of selenium in felsic volcanic-hosted massive sulphide deposits of the Yukon Territory, Canada was studied and reported by Layton- Matthews et al. (2005)."